Acquisition of English Articles by L1 Arabic Speakers - Ali Hassan, Mohamed Taha (2011)
The English article system is acknowledged to be difficult for L2 learners of the English language. Given that articles are among the most frequently used words in the English language, the difficulty increases with L2 English learners whose L1 has no articles and/or the functions of which are realised differently in the L1. The English has the definite article “the”, indefinite article “a/n” and a zero article “Ø”. The Arabic language makes use of a definite article al which corresponds to the English definite article superficially. However, the Arabic language has different ways of encoding both the notions of definiteness and indefiniteness. Because of the unique nature by which the English article system functions, many of L1 Arabic speakers have been reported to have much difficulty in acquiring the English articles all over the world (see. e.g. Bataineh 2005). As a result, the researcher has decided to investigate the use of English articles by L1 Arabic speakers. Using Huebner’s (1983) classification system, the present study aims to investigate the extent to which L1 Arabic speakers of L2 English of varying proficiency levels have acquired the definite article the, the indefinite article a/n, and the zero article Ø. The study also aims to determine the accuracy order of respondents and the nature of their interlanguage and L1 transfer in relation to results obtained by the three groups of L1 Arabic respondents. One hundred and fifty L1 Arabic respondents, drawn from three proficiency levels (advanced, upper-intermediate, and lower intermediate) were selected for the study. The selection was done based on results obtained on a proficiency test that includes the OPT (Oxford Placement Test, Allan, 1992) and the VT (Vocabulary Test, Laufer and Nation, 1999). The respondents attempted a set of study tasks, a fill-in-article test task and a forced-choice elicitation task respectively. The data obtained from the fill-in-article test was analysed quantitetively using the SPSS version18 (Statistical Package for Social Science) programme with respect to descriptive statistics in the form of frequency counts and percentages that were obtained from the analysis. A one way ANOVA was carried out to compare the general mean differences and to determine the significant differences among/between the respondents at the three levels of proficiency. For multiple comparisons, the Tukey’s Post Hoc Test was also conducted. The data was analysed in light of Huebner’s (1983) classification system and the use of articles in different item environments and with regard to the SOC (Supplied in Obligatory Contexts), TLU (Target Like Use), and UOC (Used in Obligatory Contexts) measures. The data obtained from the forced-choice elicitation were also analysed quantitatively using the SPSS by means of frequency counts and percentage scores.